A national appraisal of haemodialysis vascular access provision in Scotland. Issue 2 (March 2017) - Oliver, Scott W.; Campbell, Jacqueline; Kingsmore, David B.; Kasthuri, Ram; Metcalfe, Wendy; Traynor, Jamie P.; Fischbacher-Smith, Denis; Jardine, Alan G.; Thomson, Peter C.
Purpose: Published registry data demonstrate longstanding variation in the utilisation of different vascular access (VA) modalities between Scottish renal units; this may reflect different clinical processes between centres. A comprehensive appraisal was undertaken to understand the processes underpinning VA creation and maintenance across Scotland. Methods: A mixed methods approach was utilised. Fifty-two semi-structured interviews were conducted with patients and clinicians in all ten, adult and paediatric, Scottish renal units. Interview transcripts were subjected to thematic analysis. Clinical activity data were prospectively collected for six weeks, and correlated with registry data. Results: VA accounts for a large clinical workload. There was significant inter-centre variation in the utilisation of different VA modalities, and patients described frustrating, dissatisfying experiences. VA creation and maintenance pathways functioned best when nephrologists, surgeons and radiologists were co-located on the same campus with close multi-disciplinary working, protected clinical time, and proactive VA maintenance. No unit routinely measured or discussed procedure outcomes or strategic aspects of their service. Conclusions: Varied clinical outcomes reflected varied clinical processes. Optimised clinical pathways, staff education and measurement of clinical outcomes may improve VA service quality and facilitate safer, more effective, patient-centred care.